Acinetobacter baumannii : an evaluation of five susceptibility test methods to detect tobramycin resistance in an epidemiologically related cluster - Moodley, Vineshree Mischka (Division of Virology, 2015)
Acinetobacter baumannii is a major pathogen causing nosocomial infections, particularly in critically ill patients. This organism has acquired the propensity to rapidly develop resistance to most antibiotics. At several hospitals within Cape Town, tobramycin and colistin remain frequently the only therapeutic options. The Vitek2 automated susceptibility testing (AST) is used in the clinical laboratory to determine selected susceptibility profiles. The suspicion of a possible AST-related technical error when testing for susceptibility to tobramycin in A. baumannii precipitated this study.